If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9(2b + 8) = 0 Reorder the terms: 9(8 + 2b) = 0 (8 * 9 + 2b * 9) = 0 (72 + 18b) = 0 Solving 72 + 18b = 0 Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '-72' to each side of the equation. 72 + -72 + 18b = 0 + -72 Combine like terms: 72 + -72 = 0 0 + 18b = 0 + -72 18b = 0 + -72 Combine like terms: 0 + -72 = -72 18b = -72 Divide each side by '18'. b = -4 Simplifying b = -4
| 0.0695(-68.1)(x)+0.1(3.7)+0.059(0.22)(3.7)=0 | | y-20=-5 | | 4m=4 | | -42=-7k | | 3/c=27/9 | | 3(3f+5)=24 | | A+14=-3 | | 3-6y=0 | | f(n)=3f(n-1)+2 | | 288=18v | | n/2,400=5 | | 6m-3=3m+24 | | 0.071(-71.3)(x)+0.1(4.3)+0.059(0.22)(4.3)=0 | | B-(-2)=19 | | 5+2timesg=20 | | q-2=2 | | 40a^4-5a= | | 7y-1f=17 | | 4(y-7)=3(6+2y) | | -41=4-9r | | -x=-7x+16 | | 5b/32a2= | | y-2.3=8 | | 5/30=1x | | 180=4x+112 | | 5x-6=-2x+1 | | y+3.4=6 | | m-(-5m)-2+3m=-29 | | 3(3s+1)=2(4s+2) | | m=3/4(2,1) | | X+(-14)=-15 | | 6=m-7.8 |